TEACHER'S STRATEGY OF CHARACTERISTICS IN INSTRUMENTING CHARACTER VALUES WITH THE PROBLEM BASED LEARNING METHOD - Subaidah, Subaidah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research is motivated by the learning outcomes of Akhlak Aqidah which are not optimal, this is due to the lack of awareness of students about the importance of character values using the Problem Based Learning method. Therefore, the teacher must always accompany and remind students in instilling character values with the PBL method both in class and in application when there are problems that exist in everyday life.This study aims as follows: 1) to understand the Akidah Akhlak teacher's strategy in instilling character values using the Problem Based Learning method 2) to understand the supporting factors and inhibiting factors of the Akidah Akhlak teacher's strategy in instilling character values using the Problem Based Learning method.